Metabolically Healthy Obesity and Risk for Atrial Fibrillation: The HUNT Study. Issue 2 (3rd January 2019) - Feng, Tingting; Vegard, Malmo; Strand, Linn B.; Laugsand, Lars E.; Mørkedal, Bjørn; Aune, Dagfinn; Vatten, Lars; Ellekjær, Hanne; Loennechen, Jan P.; Mukamal, Kenneth; Janszky, Imre
Abstract : Objective: Atrial fibrillation (AF) is the most common arrhythmia and has been described as a global epidemic. Although AF is associated with both obesity and its metabolic consequences, little is known about the association between metabolically healthy obesity and AF. Methods: In a population‐based study, 47, 870 adults were followed for incident AF from 2006 to 2008 until 2015. Participants were classified according to BMI and metabolic status (using waist circumference, triglycerides, high‐density lipoprotein cholesterol, blood pressure, and glucose) at baseline. Results: During a median follow‐up of 8.1 years, 1, 758 participants developed AF. Compared with metabolically healthy individuals with BMI < 25 kg/m 2, the multivariable‐adjusted hazard ratios for metabolically healthy and unhealthy obesity were 1.6 (95% CI: 1.2 to 2.1) and 1.6 (95% CI: 1.3 to 1.9), respectively. AF risk increased according to the severity of obesity. Conclusions: Metabolically healthy and unhealthy obesity increased AF risk to a similar extent. Severity of obesity was positively associated with AF risk regardless of metabolic status.